2012
DOI: 10.1007/s10021-012-9524-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis Shows a Consistent and Strong Latitudinal Pattern in Fish Omnivory Across Ecosystems

Abstract: Several studies have demonstrated a latitudinal gradient in the proportion of omnivorous fish species (that is, consumers of both vegetal and animal material) in marine ecosystems. To establish if this global macroecological pattern also exists in fresh and brackish waters, we compared the relative richness of omnivorous fish in freshwater, estuarine, and marine ecosystems at contrasting latitudes. Furthermore, we sought to determine the main environmental correlates of change in fish omnivory. We conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
102
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 61 publications
6
102
0
5
Order By: Relevance
“…This pattern is consistent with increased plant consumption at lower latitudes by invertebrates as well (Pennings et al, 2009;Schemske et al, 2009;González-Bergonzoni et al, 2012). However, it is debated which factors drive this pattern (González-Bergonzoni et al, 2012;Ho & Pennings, 2013). Ambient temperature, the evolutionary time to adapt to plant consumption, and food availability have been evoked as important explanatory factors (González-Bergonzoni et al, 2012).…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…This pattern is consistent with increased plant consumption at lower latitudes by invertebrates as well (Pennings et al, 2009;Schemske et al, 2009;González-Bergonzoni et al, 2012). However, it is debated which factors drive this pattern (González-Bergonzoni et al, 2012;Ho & Pennings, 2013). Ambient temperature, the evolutionary time to adapt to plant consumption, and food availability have been evoked as important explanatory factors (González-Bergonzoni et al, 2012).…”
Section: Introductionsupporting
confidence: 59%
“…The prevalence of herbivory (planteating) varies with latitude: in fish communities, the level of herbivory strongly increases toward the equator (Floeter et al, 2005;Moss, 2010). This pattern is consistent with increased plant consumption at lower latitudes by invertebrates as well (Pennings et al, 2009;Schemske et al, 2009;González-Bergonzoni et al, 2012). However, it is debated which factors drive this pattern (González-Bergonzoni et al, 2012;Ho & Pennings, 2013).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…This finding suggests that the influence of temperature on the feeding preferences of ectotherms may be noticeable temporally within the same community, and not only along latitudinal gradients, as discovered in omnivorous fishes. 5 The changes in tadpole survival and life-history traits demonstrated that temperature induced changes in the relative quality of diets. While performance on animal diets strongly decreased at higher temperatures, performance on plant diets increased slightly, which may justify the shifts toward a greater assimilation of plant material during the heat waves.…”
mentioning
confidence: 99%